Continuing education of physical education teachers and self-assessment of the teaching domain - Francis Natally de Almeida Anacleto; Janaína da Silva Ferreira; Carlos Alberto Serrão dos Santos Januário; José Henrique dos Santos (Universidade Estadual Paulista (UNESP), 2017)
Abstract AIMS to diagnose continuing education initiatives and training needs of physical education teachers. The frequency, limitations and alternatives to continuing education were characterized and self-assessment areas of knowledge essential to teaching were analyzed. METHODS Data were obtained from 18 beginning teachers, using the Professional Career Characterization Questionnaire, an inventory of needs and characterization of continuing training and self-assessment of skills in areas of knowledge essential to teaching. Qualitative data were systematized and quantitative data analyzed by descriptive statistics. RESULTS Teachers performed 78 continuing training activities over the last four years, 43 in the technical area of physical education and 28 in school-based Physical Education. The most attended subjects were short-duration and graduate courses. The main limitations identified were the financial and time constraints to training. Self-assessment of the teaching areas was deemed to be sufficient, indicating a margin for new learning. CONCLUSION The teachers showed commitment to their training, with a focus on teaching and awareness of its importance in professional development.